Kinematic description of elite vs. low level players in team-handball jump throw - Wagner, H.; Buchecker, M.; von Duvillard, S. P.; Müller, E. (Journal of Sports Science & Medicine, 2010)
The jump throw is the most applied throwing technique in team- handball (Wagner et al., 2008); however, a comprehensive analysis of 3D-kinematics of the team-handball jump throw is lacking. Therefore, the purpose of our study was: 1) to measure differences in ball release speed in team- handball jump throw and anthropometric parameters between groups of different levels of performance and (2) to analyze upper body 3D-kinematics (flexion/extension and rotation) to determine significant differences between these groups. Three-dimensional kinematic data was analyzed via the Vicon MX 13 motion capturing system (Vicon Peak, Oxford, UK) from 26 male team-handball players of different performance levels (mean age: 21.2 ± 5.0 years). The participants were instructed to throw the ball (IHF Size 3) onto a target at 8 m distance, and to hit the center of a square of 1 × 1 m at about eye level (1.75 m), with maximum ball release speed. Significant differences between elite vs. low level players were found in the ball release speed (p < 0.001), body height (p < 0.05), body weight (p < 0.05), maximal trunk internal rotation (p < 0.05), trunk flexion (p < 0.01) and forearm pronation (p < 0.05) as well as trunk flexion (p < 0.05) and shoulder internal rotation (p < 0.001) angular velocity at ball release. Results of our study suggest that team-handball players who were taller and of greater body weight have the ability to achieve a higher ball release speed in the jump throw, and that an increase in trunk flexion and rotation angular velocity improve the performance in team-handball jump throw that should result in an increase of ball release speed.